Experimental and Analytical Performance Evaluation of Short Circular Hydrodynamic Journal Bearings Used in Rotary Blood Pumps. Issue 10 (2nd May 2013) - Boehning, Fiete; Timms, Daniel; Hsu, Po‐Lin; Schmitz‐Rode, Thomas; Steinseifer, Ulrich
Abstract Rotary blood pumps (RBPs) have demonstrated considerable promise while treating heart failure patients, such that they are being placed at an earlier stage of the disease. These devices may therefore be required to operate for prolonged durations which yields the need for RBPs exhibiting high durability, reliability, and blood compatibility. Noncontacting bearings, utilizing magnetic and/or hydrodynamic suspension techniques, appear to provide a suitable solution to these challenges. Hydrodynamic suspension has the advantage that it does not need feedback control systems. Among various hydrodynamic bearing types, the circular journal bearing has the particular benefit of easy manufacturing. This study presents methods to evaluate the performance of short (length to diameter ratio <1) circular hydrodynamic journal bearings (HJBs) for RBPs. Analytical calculations with specific boundary conditions are presented to predict the rotor's eccentricity under equilibrium states and thus the related performance parameters such as load capacity, power loss, and shear rates. These results and boundary conditions were confirmed experimentally in a specially designed test set‐up. The bearing performance was found to correlate to analytical solutions using the full Sommerfeld boundary condition instead of the half Sommerfeld condition conventionally used for such applications. Geometrical and operational parameter variations showed that HJB designs with a short Sommerfeld Number SS >0.02 can provide sufficient fluid film thicknesses and low shear rates. The measurements were further used to evaluate the bearings' stability. The estimation of the stability threshold drawn in relation to a modified stability index and the equilibrium eccentricity of the rotor allows the prediction of stability for short circular HJB designs under full Sommerfeld condition.